Գրաբարի հնչյունական համակարգի առանձնահատկությունները XIII դարում - Խաչատրյան, Լալիկ; Ավետիսյան, Անի (Զանգակ հրատ.)
В XIII веке фонетическая система древнеармянского языка претерпела всевозможные изменения, которые в труде “История Сюника” выражаются с помощью новых чередований фонем: гласные встречаются в виде чередования, неизвестные в грабаре (ե>ը, է(ե)>ա, օ>ու). Чередование гласных обусловлено позицией фонем и ударением. Согласные часто встречаются с качественными видоизменениями (գ>կ, բ>փ, դ>թ), которые в основном обусловлены влиянием диалектов и разговорной речи. В труде встречается также появившаяся в XIII веке новая фонема (ь), которая вощла в армянский алфавит после этого периода. Языку XIII века характерно превращение дифтонгов в монофтонги (եա>ե, աւ>օ). В XIII веке фонетическая система языка приняла особые характерные черты, которые повлияли на стойкую фонетическую систему грабара. In the 13th century the phonological system of the Classical Armenian Language underwent all the possible changes marked in terms of alternation of phonemes: the vowels occur in alternation atypical of Classical Armenian (ե>ը, է(ե)>ա, օ>ու). The vowel alternation was motivated by the position and word stress. As for the consonants, they often appear with quantitative formal changes (գ>կ, բ>փ, դ>թ), which are mainly caused by the influence of the dialects and spoken language. In the work mentioned above we come across also the monophthong ֆ which emerged in the 13th and entered the Armenian alphabet only after that period. The Armenian language of the 13th is characterized by the conversion of diphthongs to monophthongs (եա>ե, աւ>օ). In the 13th century the phonological system in use acquired specific characteristic features which eventually left a stable impact on the phonological system of grabar.
Keywords: Լեզվի պատմություն